1988
DOI: 10.1002/eji.1830180107
|View full text |Cite
|
Sign up to set email alerts
|

The function of human intercellular adhesion molecule‐1 (ICAM‐1) in the generation of an immune response

Abstract: Monoclonal antibody RR 1/1 directed against the putative LFA-1 ligand molecule intracellular adhesion molecule-1 (ICAM-1) was found to inhibit the T cell proliferative response to the antigen PPD. Interestingly, the percentage of unstimulated monocytes which expressed ICAM-1 on their surface appeared to vary greatly from person to person although the majority of monocytes did express high levels of ICAM-1 within their cytoplasm and surface expression could be rapidly induced on most cells by adherence to fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
127
4
3

Year Published

1990
1990
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(141 citation statements)
references
References 23 publications
7
127
4
3
Order By: Relevance
“…[41][42][43] Recently, CD21 has been shown to mediate homotypic and heterotypic cell binding of normal B cells and B cell lines through adhesion to its ligand, CD23. [44][45][46] Since anti-CD21 but not anti-CD23 impaired the anti-CD19-induced aggregation of B-CLL cells, CD21 appears to employ a ligand different from CD23 for this homotypic adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Recently, CD21 has been shown to mediate homotypic and heterotypic cell binding of normal B cells and B cell lines through adhesion to its ligand, CD23. [44][45][46] Since anti-CD21 but not anti-CD23 impaired the anti-CD19-induced aggregation of B-CLL cells, CD21 appears to employ a ligand different from CD23 for this homotypic adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ICAM-1 is expressed on the surface of resting peripheral blood leukocytes, and that its expression is increased by activation of monocytes, T lymphocytes, and B lymphocytes (22,23). Since 1983, we have analyzed subsets of peripheral blood mononuclear cells, including monocyte/macrophages, in patients with KD by fluorescence-activated cell sorter.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of mouse fibroblasts transfected with ICAM-1 and HLA class I1 genes show that they have a markedly enhanced ability to present antigen to human T lymphocytes, as compared with fibroblasts transfected with HLA class I1 genes only (27), and it has been suggested that ICAM-I has a function in the generation of an immune response (28). Thus, it is reasonable to postulate that fibroblasts in the RA pannus with both up-regulated JCAM-I and HLA class I1 antigens may play a major role in antigen presentation and subsequent maintenance of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%